Recent Developments in Reproductive Health Research: A Bibliometric Analysis - Indrayani, Siska; Buka, Sisilia Prima Yanuaria; Heryyanoor, Heryyanoor; Setyorini, Dhiana; Suprayitno, Emdat; Sabri, Sabri (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
In recent decades, reproductive health research has expanded significantly with growth in the number of scientific publications. This trend indicates an increased interest in understanding critical aspects affecting fertility, pregnancy problems, reproductive technologies, and their impact on women's and men's reproductive health. Bibliometric analysis is a powerful tool to understand changes in research trends, collaboration between researchers, and the impact of publications in the reproductive health domain. This study aims to analyze recent developments in reproductive health research through a bibliometric approach. The research method utilizes bibliometric analysis of leading journal databases to identify research trends, collaboration, and impact in the reproductive health domain. The results showed a significant increase in the number of publications related to reproductive health over the last few decades. Key findings include a research focus on risk factors such as diet, environment and lifestyle that affect fertility and the impact of new medical technologies on fertility treatments. In addition, cross-disciplinary collaboration is an important trend, combining fields such as medical science, psychology and social science to better understand the dynamics of reproductive health. In conclusion, this bibliometric analysis confirms the need for a holistic approach in reproductive health research. Cross-disciplinary collaboration is key to expanding understanding of the factors that influence reproductive health and to developing more effective prevention and intervention strategies. This study provides a foundation for future research planning in an effort to improve global reproductive health.